Ice Sheets and Ice Streams: Thoughts on the Cordilleran Ice Sheet Symposium - Mathews, William (Géographie physique et Quaternaire, 1991)
ABSTRACT This paper comments on preconceptions about what is meant by the terms "Cordilleran Ice Sheet" and "ice stream". Contemporary Antarctic ice streams are described. The Laurentian Channel and throughs crossing the continental ice shelf between Vancouver and Queens Charlotte Islands are suggested as candidates for the tracks of past ice streams.